2005
DOI: 10.2214/ajr.185.2.01850495
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Colonic Focal Lesions Detected by FDG PET/CT

Abstract: Presence of a focal colonic FDG uptake incidental finding on a PET/CT scan justifies a colonoscopy to detect (pre-)malignant lesions. The fusion of PET and CT images allows an accurate localization of the lesions. PET/CT is a useful tool to differentiate pathologic from physiologic FDG uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
141
3
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 172 publications
(179 citation statements)
references
References 27 publications
25
141
3
7
Order By: Relevance
“…11,13,14 The false-positive rate we found for incidental findings on PET-CT was at the high end of this range but likely reflects our selection process: all patients in our study had colonoscopies after PET-CT, whereas 30%-56% of patients with incidental colonic activity on PET-CT in other studies did not have subsequent colonoscopies. 11,13,14 In our study, because we included only those incidental findings evaluated by colonoscopy within 90 days, our rate of incidental 18 F-FDG colonic activity (0.6%) is lower than reported in earlier series. The 65% PPV of PET-CT to detect clinically significant pathology in our study is comparable to the 64%-67% PPVs reported in previous studies.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…11,13,14 The false-positive rate we found for incidental findings on PET-CT was at the high end of this range but likely reflects our selection process: all patients in our study had colonoscopies after PET-CT, whereas 30%-56% of patients with incidental colonic activity on PET-CT in other studies did not have subsequent colonoscopies. 11,13,14 In our study, because we included only those incidental findings evaluated by colonoscopy within 90 days, our rate of incidental 18 F-FDG colonic activity (0.6%) is lower than reported in earlier series. The 65% PPV of PET-CT to detect clinically significant pathology in our study is comparable to the 64%-67% PPVs reported in previous studies.…”
Section: Discussionmentioning
confidence: 74%
“…17 Incidental colonic focal 18 F-FDG uptake on PET-CT has been reported in 1.3%-2.7% of patients. 11,13,14 Although subsequent evaluations revealed significant pathology in most of these patients with incidental colonic activity, false-positive rates of 16%-33% have been reported. 11,13,14 The false-positive rate we found for incidental findings on PET-CT was at the high end of this range but likely reflects our selection process: all patients in our study had colonoscopies after PET-CT, whereas 30%-56% of patients with incidental colonic activity on PET-CT in other studies did not have subsequent colonoscopies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations